(untitled) (Analysis in Theory and Applications, 2013)
In this paper, we establish two integral inequalities for Hardy operator's conjugate operator at the endpoint on n-dimensional space. The operator H^*_n is bounded from L^1_x^α(G^n) to L^q_x^β(G^n) with the bound explicitly worked out and the similar result holds for H^*_n.